ANALYSIS OF RAINFALL AND DROUGHT CLIMATOLOGY FOR CROP PLANNING IN SUBTROPICAL PLAINS OF CHATHA, JAMMU - MUKHTAR , AHMED; SONAM , LOTUS; D, RAJALAKSHMI; SHIVINDER , SINGH; A. V. M., SUBHA RAO (MAUSAM, 2020)
Although the subject area of climate change is vast, the changing pattern of rainfall is a topic within this field that deserves urgent and systematic attention, since it affects both the availability of freshwater and food production (Dore, 2005). Climate change is one of the key global challenges in the present era. It refers to a statistically significant variation in either the mean state of the climate or in its variability, persisting for an extended period typically decades or long (World Meteorological Organization). According to Fourth Assessment Report of Intergovernmental Panel on Climate Change, the world indeed has become more drought prone with higher frequencies of extreme events.